A 28-day Gavage Toxicity Study in Male Fischer 344 Rats with 2-methylfuran. (February 2014) - Gill, Santokh S.; Kavanagh, Meghan; Cherry, Wendy; Barker, Michael; Weld, Madeline; Cooke, Gerard M.
In most thermally treated products, a series of alkylated furan derivatives have been found, in particular 2-substituted alkylfurans such as 2-methylfuran. These methyl analogs are metabolically activated in a similar fashion as the parent furan, yielding highly reactive unsaturated dialdehydes. There is currently limited toxicological data available for 2-methyl furan exposure by any route that makes conducting a risk assessment difficult. In this pilot study, we report the general toxicology findings affecting tissue morphology, histopathology, clinical biochemistry, and hematology in a 28-day gavage study. The liver was the primary target organ that developed dose-dependent toxicity. Relative liver weights were increased by 42% at 25.0 mg/kg/body weight (bw)/day. Histological changes in the liver were observed at 0.4, 1.5, 3.0, 6.0, 12.0, and 25.0 mg/kg bw/day. These changes were not accompanied by clinical changes in the serum enzyme markers such as alanine transaminase, alkaline phosphatase, and aspartate transaminase. Clinical biochemistry markers for kidney were altered, but these were not accompanied by histological changes. The prostate was significantly decreased in size at the 25.0 mg/kg bw/day dose of 2-methyfuran. Some hematological parameters were also altered.